Detection of PD-L1 in the urine of patients with urothelial carcinoma of the bladder - Georgi Tosev (Nature Portfolio, 2021)
Abstract There are currently five programmed death-1 (PD-1)/programmed death ligand-1 (PD-L1) inhibitors approved for the treatment of locally advanced or metastatic urothelial carcinoma (UC) of the bladder. For platinum-ineligible patients, testing of tumor specimens for PD-L1 expression is required. However, scoring of PD-L1 immunohistochemistry is complex due to different antibodies used, the requirement to score expression in different cellular compartments and intratumoral heterogeneity. It can also be difficult to obtain and test longitudinal tumor samples, which would be desirable to monitor treatment responses and tumor evolution under treatment-induced selective pressure. In the present proof-of concept study, we provide evidence that PD-L1 can be detected in the urine of patients with non-muscle invasive bladder cancer (NMIBC) and muscle-invasive bladder cancer (MIBC). Urine PD-L1 levels were significantly higher in NMIBC and MIBC patients when compared to patients with various non-malignant urological diseases. Further prospective and independent studies are required to assess the value of PD-L1 in the urine as a novel biomarker with potential for the early detection, prediction and therapeutic monitoring of patients with UC of the bladder.